Strategi Guru Pendidikan Islam Dalam Menanamkan Nilai-Nilai Keislaman Pada Generasi Z - Annisa Hidayati; Alia Nadira; Dwita Saskia; Tuti Nuriyati (TA'DIBAN, 2025)
Generation Z as a digital generation has unique characteristics such as high-tech capabilities, multitasking, and dependence on social media, which are challenges in the educational process, especially in instilling Islamic values. This study aims to examine the strategies that can be applied by Islamic values in this generation. The method used is literature research with a qualitative approach, through the analysis of various academic literature related to learning strategies, educational technology, and the characteristics of generation Z. The results of the study show that effective learning strategies must be adaptive, innovative, and technology-based, such as the use of blended learning, social media, learning applications, visual methods, and approaches that foster creativity and entrepreneurial values. In addition, the role of PAI teachers as educators, role models, motivators, and evaluators is very important in instilling Islamic values contextually. In conclusion, the success of instilling Islamic values in Generation Z is highly dependent on the ability of teachers to align learning approaches with the needs and digital lifestyles of this generation. Keywords: Strategy, values, islam